Signals in the Soil Developments in Internet of Underground Things - Salam, Abdul; Raza, Usman; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book provides an in-depth coverage of the most recent developments in the field of wireless underground communications, from both theoretical and practical perspectives. The authors identify technical challenges and discuss recent results related to improvements in wireless underground communications and soil sensing in Internet of Underground Things (IOUT). The book covers both existing network technologies and those currently in development in three major areas of SitS: wireless underground communications, subsurface sensing, and antennas in the soil medium. The authors explore novel applications of Internet of Underground Things in digital agriculture and autonomous irrigation management domains. The book is relevant to wireless researchers, academics, students, and decision agriculture professionals. The contents of the book are arranged in a comprehensive and easily accessible format. Focuses on fundamental issues of wireless underground communication and subsurface sensing; Includes advanced treatment of IOUT custom applications of variable-rate technologies in the field of decision agriculture, and covers protocol design and wireless underground channel modeling; Provides a detailed set of path loss, antenna, and wireless underground channel measurements in various novel Signals in the Soil (SitS) testbed settings.
Introduction -- Part 1: Physical Layer for Wireless Underground Communications -- Introduction to Wireless Underground (UG) Communications -- Electromagnetic Characteristics of the Soil -- Wireless Underground Channel Modeling -- Part 2: Underground Antenna and Radio Interface Technologies -- Modulation Schemes -- Channel Bandwidth and Capacity -- Energy Harvesting -- Underground Antenna Design -- UG Phased Arrays and Beamforming -- Diversity Reception -- Part 3: Novel Soil Sensing Techniques -- Soil Sensing -- Soil Moisture and Permittivity Estimation -- Zenneck Waves on Soil Surface -- Part 4: IOUT Applications in Urban Underground Infrastructure -- Monitoring and Real-time Soil Monitoring and Irrigation Automation -- Internet of Underground Things Advancements -- Digital Agriculture -- Autonomous Irrigation Management Architecture -- Urban Underground Infrastructure Monitoring -- Part 5: Recent Advances in Testbed Design and Implementation -- Empirical Results -- Conclusion.
Keywords: Signal processing; Image processing; Speech processing systems; Electrical engineering; Computer communication systems; Microwaves; Optical engineering; Signal, Image and Speech Processing; Communications Engineering, Networks; Computer Communication Networks; Microwaves, RF and Optical Engineering